An Update On Proficiency of Voltage-gated Ion Channel Blockers in the Treatment of Inflammation-associated Diseases - Kelkar, Siddesh; Nailwal, Namrata; Bhatia, Nirav Y.; Doshi, Gaurav; Sathaye, Sadhana; Godad, Angel Pavalu (Current Drug Targets, 2022)
Inflammation is the body’s mechanism to trigger the immune system, thereby preventing bacteria and viruses from manifesting their toxic effect. Inflammation plays a vital role in regulating inflammatory mediator levels to initiate the wound healing process depending on the nature of the stimuli. This process occurs due to chemical release from white blood cells by elevating blood flow to the site of action, leading to redness and increased body temperature. Currently, there are numerous Non-steroidal anti-inflammatory drugs (NSAIDs) available, but these drugs are reported with adverse effects such as gastric bleeding, progressive kidney damage, and increased risk of heart attacks when prolonged use. For such instances, alternative options need to be adopted. The introduction of voltage-gated ion channel blockers can be a substantial alternative to mask the side effects of these currently available drugs. Chronic inflammatory disorders such as rheumatoid and osteoarthritis, cancer and migraine, etc., can cause dreadful pain, which is often debilitating for the patient. The underlying mechanism for both acute and chronic inflammation involves various complex receptors, different types of cells, receptors, and proteins. The working of voltage-gated sodium and calcium channels is closely linked to both inflammatory and neuropathic pain. Certain drugs such as carbamazepine and gabapentin, which are ion channel blockers, have greater pharmacotherapeutic activity for sodium and calcium channel blockers for the treatment of chronic inflammatory pain states. This review intends to provide brief information on the mechanism of action, latest clinical trials, and applications of these blockers in treating inflammatory conditions.
Keywords: inflammatory conditions